2020
DOI: 10.1002/uog.21981
|View full text |Cite
|
Sign up to set email alerts
|

Imaging in gynecological disease (20): clinical and ultrasound characteristics of adnexal torsion

Abstract: Objectives To describe the clinical and ultrasound characteristics of adnexal torsion. Methods This was a retrospective study. From the operative records of the eight participating gynecological ultrasound centers, we identified patients with a surgically confirmed diagnosis of adnexal torsion, defined as surgical evidence of ovarian pedicle, paraovarian cyst and/or Fallopian tube twisted on its own axis, who had undergone preoperative ultrasound examination by an experienced examiner, between 2008 and 2018. O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
60
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 53 publications
(70 citation statements)
references
References 62 publications
(102 reference statements)
8
60
0
2
Order By: Relevance
“…Lee et al 13 demonstrated that in 16 of 28 patients with a diagnosis of torsion at surgery, both arterial flow and venous flow were identified in the pedicle on color Doppler evaluations and were highly correlated with ovarian viability. Moro et al 11 showed a higher prevalence of identification of the whirlpool sign (90.8%). We speculate that the higher prevalence of identification of the whirlpool sign in the study by Moro et al 11 may have been related to the exclusion of 162 of 315 (51%) of cases because of inadequate images and a method wherein only surgically proven cases of adnexal torsion were included.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…Lee et al 13 demonstrated that in 16 of 28 patients with a diagnosis of torsion at surgery, both arterial flow and venous flow were identified in the pedicle on color Doppler evaluations and were highly correlated with ovarian viability. Moro et al 11 showed a higher prevalence of identification of the whirlpool sign (90.8%). We speculate that the higher prevalence of identification of the whirlpool sign in the study by Moro et al 11 may have been related to the exclusion of 162 of 315 (51%) of cases because of inadequate images and a method wherein only surgically proven cases of adnexal torsion were included.…”
Section: Discussionmentioning
confidence: 94%
“…Moro et al 11 showed a higher prevalence of identification of the whirlpool sign (90.8%). We speculate that the higher prevalence of identification of the whirlpool sign in the study by Moro et al 11 may have been related to the exclusion of 162 of 315 (51%) of cases because of inadequate images and a method wherein only surgically proven cases of adnexal torsion were included. In our study, this finding was retrospectively identified in an additional 18 patients during the cine loop review, which suggests that actively searching for this sign may improve its detection.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Intervening regions of increased echogenicity may indicate hemorrhagic infarction (49). The follicle-containing cortex becomes stretched around the periphery of the medulla, creating a thin layer of follicles that resembles a string of pearls, which is visible as multiple hypoechoic avascular cystic structures (Fig 9) (39). An additional sonographic finding is that of a hyperechoic rim surrounding peripherally displaced antral follicles, known as the "follicular ring" sign, with the rim measuring 1-2 mm in thickness (50).…”
Section: Us Assessmentmentioning
confidence: 99%
“…US facilitates dynamic assessment in multiple planes to identify this finding as the characteristic "whirlpool" (twisting of the hypoechoic vessels with or without a color Doppler signal) or "target" (concentric alternating hypo-and hyperechoic rings) sign if it is visualized perpendicular to the rotational axis (Figs 2, 10). Although this sign is present in more than 90% of confirmed cases of adnexal torsion (39), it can be subtle, depending on the number of twists and structures involved (51).…”
Section: Us Assessmentmentioning
confidence: 99%